Engine Head Thermal Loading - Froukh, Ibrahim; Amleh, Alaa (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2007)
The internal combustion IC engine is a heat engine that converts chemical energy in a fuel into mechanical energy , usually made of available on a rotating output shaft ........
no of pages 95 , ميكانيك 12/2007 , in the store
Keywords: Engine Head Thermal